Esterase patterns of species in the Drosophila buzzatii cluster. - Lapenta, A. S. [UNESP]; de Campos Bicudo, H. E. [UNESP]; Ceron, C. R. [UNESP]; Cordeiro, J. A. [UNESP] (My University, 1995)
A comparative analysis was made of the esterase isoenzyme patterns of eight iso-female lines, four of Drosophila serido (B31 D1, A55, B59, Q1, B50Q3), two of D. koepferae (B20D2 and B25D7), one of D. seriema (A95) and one of D. buzzatii (Buz). In all, 43 bands in the spectrum of esterase isoenzymes were detected by electrophoresis in polyacrylamide gels. They showed variations in specific reactions with alpha and beta-naphthyl acetate, number of patterns yielded in their intra-isofemale line combinations, frequencies of such combinations and the thickness and staining degree of some bands, in different individuals, lines and species. Among bands detected exclusively in males, seven may be considered sex-specific (5 alpha-esterases and 2 beta-esterases). These male-specific alpha-esterases have in common the inability to cleave beta-naphthyl acetate in the absence of alpha-naphthyl, denoting a possible common function. The similarity index (SI) and analysis of dependence were calculated in an attempt to quantify the differentiation of the iso-female lines studied, on the basis of esterase bands. SI mean value allowed the separation of the isofemale lines into five classes. Each species had its own pattern of esterase bands, but some bands were shared. A divergence hypothesis for the isofemale lines and the species is discussed.